INDUSTRI RUMAH TANGGA NUGGET BABI DALAM UPAYA MENINGKATKAN PEREKONOMIAN MASYARAKAT DI DESA BLAHKIUH - B.R.T., Putri; ardani, N L. G. Sum; Wibawa, AA P. (Buletin Udayana Mengabdi; Vol 10 No 1 (2011): Volume 10 No.1 – April 2011, 2012)
This Community service was held on Friday, September 19th 2008 in Balai Banjar Ulapan 1 Blahkiuh Village, District Abiansemal, Badung Regency. It aimed to increase farmers’ knowledge about new innovation and technology in processing field of ranch result. This activity applied two methods, namely counseling and direct application. Participants who attended the counseling session were given about agribusiness, and discussion about the existing problems faced by farmer. Besides, they were given information about ways of processing pork meat to be nugget with its economic perspectives. Application method was conducted by practicing to make pork nugget attended by the PKK members. Conclusion can be taken that this activity was warmly welcome by the Head of Village and staff, farmers and PKK society who were present then. All participants were diligent and responsive attending the counseling. This can be seen from many questions raised during the discussion time. Economic analysis was done on pork meat processing to become nugget which indicated satisfactory result, by profit level reaching 162%. Suggestion can be given that counseling activities along with direct practice continuously, the farmer and society who used not to know theoretically are able to use the new technology